A longitudinal study of vaccine hesitancy attitudes and social influence as predictors of COVID-19 vaccine uptake in the US. Issue 5 (30th November 2022) - Latkin, Carl; Dayton, Lauren; Miller, Jacob; Yi, Grace; Balaban, Ariel; Boodram, Basmattee; Uzzi, Mudia; Falade-Nwulia, Oluwaseun
ABSTRACT: Background: In many countries with high levels of COVID-19 vaccine access, uptake remains a major issue. We examined prospective predictors of COVID-19 vaccine uptake in a United States longitudinal study. Methods: An online longitudinal study on COVID-19 and well-being assessed vaccine hesitancy attitudes, social norms, and uptake among 444 respondents who had completed both survey waves in March and June 2021. Results: The mean sample age was 41, with 55% female, 71% white, 13% Black, and 6% Latinx. In March 2021, 14% had received at least one COVID-19 vaccine dose. By June 2021, 64% reported receiving at least one dose. In prospectively assessing predictors of vaccine uptake, we found strong correlations among five different vaccine hesitancy questions. In multivariable logistic regression models, family and friends discouraging vaccination (adjusted odds ratios [aOR] = .26, 95% CI = .07, .98), not knowing whom to believe about vaccine safety (aOR = .51, 95% CI = .27, .95), and concerns that shortcuts were taken with vaccine development (aOR = .43, 95% CI = .23, .81) were all independent predictors of lower vaccine uptake. Political conservatism, gender, education, and income were also independent predictors of reduced uptake. Vaccine hesitancy items were also modeled as a scale, and the scale was found to be strongly predictive of vaccine uptake. Conclusions: The findings highlight the importance of social norm interventions and suggest general and specific vaccine hesitancy attitudes, especially trust, should be considered in developing vaccine uptake programs.